Deteksi Cepat Fusarium sp. pada Benih Kedelai Menggunakan Metode Spektroskopi Fluoresens - Djoko Pujiarto; Bonny Poernomo Wahyu Soekarno; Akhiruddin Maddu (Jurnal Fitopatologi Indonesia, 2018)
Rapid Detection Method for Fusarium sp. on Soybean Seed Using Fluorescence Spectroscopy MethodSeed borne pathogens play an important role as source of inoculum for disease in the field.  Seed health testing is applied in order to prevent risks caused by seed borne pathogen. Fluorescence spectroscopy is a potential technology to be used as detection method for seed borne pathogen. Research was conducted to develop rapid detection protocol for seed borne pathogenic fungus by fluorescence spectroscopy method.  The result showed that fluorescence spectroscopy could detect fluorescence emission of metabolite of Fusarium sp. after soybean seeds were incubated for 24 hr.  Metabolite of Fusarium sp. produced cyan fluorescent at peak wavelength emission 504 nm when excited to violet light (405 nm).  Fusarium sp. displayed typical fluorescence emission spectra which differ from fluorescence emission spectra of growth medium potato dextrose broth (PDB) (502 nm). It was evidenced that fluorescence spectroscopy method can be used to detect pathogenic seed borne fungi.